2021
DOI: 10.18632/aging.203558
|View full text |Cite
|
Sign up to set email alerts
|

A2E-induced inflammation and angiogenesis in RPE cells in vitro are modulated by PPAR-α, -β/δ, -γ, and RXR antagonists and by norbixin

Abstract: N -retinylidene- N -retinylethanolamine (A2E) plays a central role in age-related macular degeneration (AMD) by inducing angiogenesis and inflammation. A2E effects are mediated at least partly via the retinoic acid receptor (RAR)-α. Here we show that A2E binds and transactivates also peroxisome proliferator-activated receptors (PPAR) and retinoid X receptors (RXR). 9’- cis -norbixin, a di-apocarotenoid is also a ligand of these nuclear receptors (NR). No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 50 publications
(105 reference statements)
2
26
0
Order By: Relevance
“…181 Fontaine et al found that A2E promoted inflammation and angiogenesis partially via inducing the transactivation of PPARs and retinoid X receptors (RXR) in RPE cells. 185,186 PPARγ coactivator (PGC)-1α is a protein that increases RPE metabolism, maintains mitochondrial homeostasis, and protects against ROS damage. 187 Zhang et al found that PGC-1α −/− mice on a high-fat diet were more prone to developing AMD.…”
Section: Lcpufa Peroxidation and Its Effects On Inflammation In Amdmentioning
confidence: 99%
“…181 Fontaine et al found that A2E promoted inflammation and angiogenesis partially via inducing the transactivation of PPARs and retinoid X receptors (RXR) in RPE cells. 185,186 PPARγ coactivator (PGC)-1α is a protein that increases RPE metabolism, maintains mitochondrial homeostasis, and protects against ROS damage. 187 Zhang et al found that PGC-1α −/− mice on a high-fat diet were more prone to developing AMD.…”
Section: Lcpufa Peroxidation and Its Effects On Inflammation In Amdmentioning
confidence: 99%
“…Norbixin modulates inflammation, as demonstrated by its inhibitory effect on A2E-induced expression of IL-6 and IL-8 and by its effect on the transactivation of NF-κB and AP-1. In addition, our previous observations demonstrated that norbixin impairs VEGF expression induced by A2E [ 5 ]. Norbixin also reduces the accumulation of A2E by primary porcine RPE cells in vitro [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral complementation with norbixin also reduces A2E and lipofuscin accumulation in RPE cells in these animals [ 7 ]. The beneficial effects of norbixin are potentially associated with its interaction with several nuclear receptors: PPAR-γ, PPAR-α, PPAR-β/δ, and also RXR-α [ 5 , 8 ]. We proposed that norbixin behaves as a neutral antagonist of these nuclear receptors, thus inhibiting their transactivation induced by A2E [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of AKT leads to the expression of inflammatory cytokines (IL-6, IL-8, IL-18), which support the inflammatory environment involved in AMD pathogenesis, and contributes to VEGF secretion by the inflammatory-induced angiogenesis process [ 34 ]. Previous study has revealed that RGA, as an anti-inflammatory formulation, could modulate the expression of inflammatory cytokines such as IL-6 and IL-8 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%